Continuous Intravenous Anesthesia by Dextroketamine and Detomidine in Bitches Subjected to Ovariohysterectomy and Premedicated with Midazolam and Morphine - Vieira Henrique, Fernanda; Santos Pereira, Sóstenes Arthur Reis; Gomes de Medeiros, Lylian Karlla; Figueirêdo Batista, Luanna; de Azevedo Silva, Jardel; da Silva Xavier de Olivei, Lídia Virgínia; de Araújo Dias, Diane Cristina; Pereira de Souza, Almir; da Nóbrega Neto, Pedro Isidro (Acta Scientiae Veterinariae, 2019)
Background:The use of injectable anesthetics to induce and maintain anesthesia has been the subject of extensive research. Ketamine induces dissociative anesthesia, which is characterized by sensory loss, analgesia and amnesia without loss of consciousness. The levorotatory isomer of ketamine is dextroketamine. Detomidine, a potent myorelaxant that acts as a sedative and analgesic, is commonly used on horses but rarely tested in dogs. The purpose of this study was to evaluate the cardiorespiratory and anesthetic effects promoted by a combination of detomidine and dextroketamine applied via continuous intravenous infusion in bitches premedicated with midazolam and morphine. Materials, Methods & Results:Eight bitches treated at the veterinary hospital of the Federal University of Campina Grande were referred for elective ovariohysterectomy (OHE). The animals were premedicated with 0.3mg/kg of midazolam and 0.1mg/kg ofmorphine intramuscular (IM) followed, after 15 min, with 0.02mg/kg of detomidine IM. Fifteen min after the administration of detomidine, 3.5 mg/kg of dextroketamine was administered intravenously (IV), followed by continuous IV infusion of 14 mg/kg/h of dextroketamine and 30 μg/kg/h of detomidine. Heart rate (HR), respiratory rate (RR), body temperature (BT), mean arterial pressure (MAP), myorelaxation and electrocardiogram were recorded before and 15 min after the administration of midazolam and morphine (M0 and M1), 15 min after detomidine (M2), immediately after starting the infusion (M3), at 10 min intervals up to 60 min (M4, M5, M6, M7, M8 and M9) and 30 min after the end of the infusion (M10). Blood gas variables were analyzed at M0, M1, M2, M6, M9 and M10. Analgesia was evaluated by measuring cortisol and glucose levels at M0, three min after dermotomy, three min after clamping the ovarian pedicle, and three min after dermorrhaphy. The quality and duration of recovery were evaluated. HR dropped significantly from M2 to M4 (P <0.05), with bradycardia recorded at M2; at RR, with bradypnea starting at M2; and at BT from M6 to M10 (P<0.05), without severe hypothermia. Mean arterial pressure (MAP) increased significantly from M3 to M7 (P<0.01). Hypotension was observed at M1. The following were also observed: high amplitude T wave, elevated ST segment, atrioventricular blocks, sinus arrest and premature ventricular complexes. The blood gas variables suggested the presence of respiratory acidosis with hypoxemia. Cortisol levels were significantly higher (P<0.01) after clamping the ovarian pedicle (6.23 ± 3.07μg/dL) and after dermorrhaphy (6.03 ± 2.24μg/dL) than the levels at M0 (1.74 ± 1.08μg/dL). Glucose levels three min after dermorrhaphy (129.46 ± 29.61mg/dL) were substantially increased (P<0.05) in comparison to M0 (89.66 ± 7.92mg/dL). Myorelaxation was significantly higher from M3 to M9 (P<0.05) than at M0 and M1. The recovery period lasted 302.1 ± 64.9 min. The quality of recovery was considered excellent in two animals, good in four animals and poor in two animals, which showed signs of agitation, vocalization and hypersalivation. Discussion:Continuous intravenous anesthesia with dextroketamine and detomidine causes cardiorespiratory depression, promoting good muscle relaxation. Based on the findings of serum cortisol, blood glucose, blood pressure and augmented infusion rate, it can be stated that the protocol used here cannot eliminate the pain caused by OHE in bitches.